Clinical characteristics and outcome of biopsy-proven myocarditis in children - results of the German prospective multicentre registry “MYKKE” - Seidel, Franziska; Opgen-Rhein, Bernd; Rentzsch, Axel; Boehne, Martin; Wannenmacher, Bardo; Boecker, Dorotheé; Reineker, Katja; Grafmann, Maria; Wiegand, Gesa; Hecht, Tobias; Kiski, Daniela; Fischer, Marcus; et al. (International journal of cardiology, 2022)
Background - Heart failure (HF) due to myocarditis might not respond in the same way to standard therapy as HF due to other aetiologies. The aim of this study was to investigate the value of endomyocardial biopsies (EMB) for clinical decision-making and its relation to the outcome of paediatric patients with myocarditis. - Methods - Clinical and EMB data of children with myocarditis collected for the MYKKE-registry between 2013 and 2020 from 23 centres were analysed. EMB studies included histology, immunohistology, and molecular pathology. The occurrence of major adverse cardiac events (MACE) including mechanical circulatory support (MCS), heart transplantation, and/or death was defined as a combined endpoint. - Results - Myocarditis was diagnosed in 209/260 patients: 64% healing/chronic lymphocytic myocarditis, 23% acute lymphocytic myocarditis (AM), 14% healed myocarditis, no giant cell myocarditis. The median age was 12.8 (1.4-15.9) years. Time from symptom-onset to EMB was 11.0 (4.0-29.0) days. Children with AM and high amounts of mononuclear cell infiltrates were significantly younger with signs of HF compared to those with healing/chronic or healed myocarditis. Myocardial viral DNA/RNA detection had no significant effect on outcome. The worst event-free survival was seen in patients with healing/chronic myocarditis (24%), followed by acute (31%) and healed myocarditis (58%, p = 0.294). A weaning rate of 64% from MCS was found in AM. - Conclusions - EMB provides important information on the type and stage of myocardial inflammation and supports further decision-making. Children with fulminant clinical presentation, high amounts of mononuclear cell infiltrates or healing/chronic inflammation and young age have the highest risk for MACE.